Environmental costs in the management of solid waste in the general hospitals of the city of Loja 2014 - 2015 - Hurtado Ordóñez, Ruth Cecilia (2018)
Objective: To determine how environmental costs affect the management of solid waste in the general hospitals of the city of Loja. Method: Quantitative approach, based on statistical analysis and procedures, with deductive reasoning that allowed achieving a result, the investigation has a correlational scope. It facilitates knowing the cause and effect between the variables environmental costs and solid waste management. It is an empirical investigation because it is an event that has been presented in the institution and applied because an alternative solution is proposed to face the problem. Results: Stratified sampling was used, a Spearm's Rho correlation of 926 was obtained. Conclusions: there is a positive, strong and direct correlation between the variables: environmental costs and solid waste management in the General Hospitals of the city of Loja.